The Effectiveness of Audio Communicative Blended Method of Second Language Teaching at Secondary Level - Rifdha, M.S.F.; Paranthaman, V. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study examines the effectiveness of Audio Communicative Blended Methodology (ACBM) in secondary-level language instruction, integrating the structural rigor of the Audio-Lingual Method (ALM) with the interactive features of Communicative Language Teaching (CLT). The research investigates how the combination of ALM’s repetitive, form-focused approach with CLT’s context-based communication fosters language learning outcomes. A mixed-method design was employed, incorporating both qualitative and quantitative data. Participants comprised ten Grade 8 students who engaged in five task types: audio story-based tasks, role-plays with written dialogue, picture descriptions with audio prompts, travel guide activities, and roleplays in everyday scenarios. Data collection instruments included pre-tests, post-tests, classroom observations, and questionnaires. Pre-tests assessed baseline proficiency, post-tests measured language improvement, observations tracked engagement, and questionnaires captured both student and teacher perceptions of ACBM. The findings revealed significant gains in language proficiency, with students demonstrating enhanced engagement, confidence, and the ability to apply language skills in real-life contexts. Teachers reported a positive shift in instructional practices, emphasizing the benefits of integrating audio input with communicative tasks. Overall, ACBM proved effective in balancing structural accuracy with communicative fluency, thereby offering a dynamic and adaptable model for secondary-level language teaching.
Keywords: Audio communicative blended methodology; Audio-lingual method; Communicative language teaching; Mixed methods; Secondary education; Language instruction